Riwayat Mawaakib al-Ahrar li Najiib al-Kailanii: Diraasat Tahliiliyyat Siimiyaaiyyat 'Inda Roland Barthes: رواية "مواكب الأحرار" لنجيب الكيلاني : دراسة تحليلية سيميائية عند رولاند بارتس - Anggraini, Novita; Syamsul Anam; Asep Maulana (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The aims to uncover the significance within the novel Mawakib Al-Ahrar using Roland Barthess theoretical framework. Roland Barthes divides meaning into three, namely denotation meaning, connotation meaning, and myth. This research uses a descriptive qualitative study with a study literature type. The main data originates from the novel Mawakib Al-Ahrar, while supplementary data is derived from books, journals, and relevant literature. Data collection method use documentation and study literature and data analysis thechniques use content analysis techniques. The result of the study reveal that the novel Mawakib Al-Ahrar is rich in denotational meaning, connotative meaning, and mythical meaning. The meaning contained is very clearly depicted in the novel, with a story narrative that is easy for readers to understand. Of all the meanings contained in the novel, it refers to one word with the theme of the novel, namely jihad. The denotational meaning of the jihad is being serious in the way of Allah. The connotation means the never-ending spirit that Haji musthafa Busytaili had not to give up and hand over his country to the invaders. Fully supported by syeikh Ali Junjaihi, he even took part ini freeinh Haji Musthafa from French prison by advising Husein to give ransom to Barthalami (an ambitios and rank-crazy French accomplice) because he thought Musthafa Busytaili was part the rebels. الملخص الهدف من هذا البحث لمعرفة المعنى الذي تحتويه رواية مواكل الأحرار من خلال نظرية رولان بارت، يقسم رولان بارت المعنى إلى ثلاثة وهي معنى القاموسي، ومعنى الضمني، والأسطورة. يستخدم هذا البحث دراسة وصفية نوعية مع نوع دراسة الأدب. مصدر البيانات الأساسي هو رواية مواكب الأحرار ومصادر البيانات الثانوية تأتي من الكتاب والمجلات والأدبيات ذات الصلة. تستخدم أساليب جمع البيانات التوثيق ودراسة الأدابيات وتقنيات تحليل البيانات تستخدم تقنيات تحليل المحتوى. وأظهرت نتائج البحث أن رواية مواكب الأحرار غنية بالمعنى القاموسي والمعنى الضمني والمعنى الأسطورة. تم تصوير المعنى الموجود في الرواية بشكل واضح للغاية، مع سرد القصة يسهل على القراء فهمه. ومن بين جميع المعاني التي تحتويها الرواية، فهي تشير إلى كلمة واحدة تحمل ووضوع الرواية يعني الجهاد. المعنى القاموسي هو الجهاد في سبيل الحق. المعنى الضمني الوارد في رواية "مواكب الأحرار" لنجيب الكيلاني هو الحماسة دون الإستسلام من الشخصية الرئيسة والتنازل عن بلده للاستعمار. مدعوما كاملا من أصدقائه العديدة، وبالخصوص الشيخ علي الجنجيهي، المشترك حتى في تحرير الحاج المصطفى من الحبس بطريقة نصيحة حسين بإعطاء فدية لبرطلمي (يناصر الأعداء للمستعمر الفرنسي) لأنه البشتيلي يعتبرالمحركون للمتمردين. ومعنى الأسطورة أنه ليس هناك أعضم من تضحية الإنسان في سبيل أمته و دينه دليلا على أنه يحب وطنه و دينه حقا، و مستعد للتضحية حتى لو كانت حياته على المحك. مجاهد لم يستسلم أبدا تهت أي ظرف من الظرف.